Pendampingan dan Penguatan UMKM Batik Tulis Karangjati Pandaan Melalui Engagement Marketing Social Media - Miftahul Huda (Institute for Research and Community Service in Universitas Yudharta Pasuruan, 2019)
Marketing constraints and limited skilled person are problems with Batik “Jati Asih”, so that it is less known by the wider community. The problems faced can be minimized by utilizing appropriate marketing. This study uses the Participatory Action Research (PAR) approach. Mentoring and strengthening UMKM of the Batik Tulis Karangjati Pandaan through social media marketing engagement has become a solution for the players UMKM of the Batik Tulis Karangjati. UMKM Batik Tulis players who took part in this assistance increasingly understood the importance of social media in marketing their products. This is proven by several products that have been sold through the market place that has made.